2020
DOI: 10.1371/journal.pone.0233126
|View full text |Cite
|
Sign up to set email alerts
|

Robust two-stage influenza prediction model considering regular and irregular trends

Abstract: Influenza causes numerous deaths worldwide every year. Predicting the number of influenza patients is an important task for medical institutions. Two types of data regarding influenza-like illnesses (ILIs) are often used for flu prediction: (1) historical data and (2) user generated content (UGC) data on the web such as search queries and tweets. Historical data have an advantage against the normal state but show disadvantages against irregular phenomena. In contrast, UGC data are advantageous for irregular ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Our results showed the correlations for the LCI and LCIPP demonstrate external validity, as they were both associated with constructs that could be explained by previous research. This study joins a growing body of literature that uses web-based search queries to track public health (eg, Murayama et al [32]), and the LCIPP adds the dimension of using prefecture-level infection rates to control for expected outcomes. Therefore, this study was able to effectively quantify public concern at a deeper level, which we propose is explained by the collectivistic psychological tendencies of a society.…”
Section: Effectiveness Of Search Queries As Public Concern Indicatorsmentioning
confidence: 99%
“…Our results showed the correlations for the LCI and LCIPP demonstrate external validity, as they were both associated with constructs that could be explained by previous research. This study joins a growing body of literature that uses web-based search queries to track public health (eg, Murayama et al [32]), and the LCIPP adds the dimension of using prefecture-level infection rates to control for expected outcomes. Therefore, this study was able to effectively quantify public concern at a deeper level, which we propose is explained by the collectivistic psychological tendencies of a society.…”
Section: Effectiveness Of Search Queries As Public Concern Indicatorsmentioning
confidence: 99%
“…Our model is motivated by the idea that search query data are useful features for forecasting non-seasonal parts of flu data. This concept originates from a previous study [35], which reported that the flu forecasting accuracy is improved by splitting the forecasting part from the historical ILI data and search query data. The model architecture is presented in Fig.…”
Section: Model Structurementioning
confidence: 99%
“…-Two-stage: The Two-stage model [35], composed of long short-term model and AR model, was developed inspired by a similar idea to ours, in that the usefulness of the input data differs; historical ILI data and search query data are useful for forecasting the seasonality and trend, respectively. For the multi-step-ahead forecast, we extended the two-stage model to the encoderdecoder architecture.…”
Section: Comparative Models -Grumentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal influenza, caused by the influenza virus, is an acute respiratory disease characterized by the sudden onset of fever, headache, cough, rhinitis, and muscle and joint pain [1,2]. Influenza can be classified into four types: influenza A virus, influenza B virus, influenza C virus, and influenza D virus, among which influenza virus types A and B circulate and cause seasonal influenza [3].…”
Section: Introductionmentioning
confidence: 99%